TransOral Robotic Surgery for Obstructive Sleep Apnea A Practical Guide to Surgical Approach and Patient Management - Vicini, Claudio; Hoff, Paul T.; Montevecchi, Filippo (Springer International Publishing : Imprint: Springer, 2016)
This comprehensive book pulls together the essential elements needed to assess sleep apnea patients for the transoral robotic surgical approach and how to optimize the surgery. Detailed information on patient selection, pre-operative work up, anesthesiological pre and post-operative management, surgery, complication prevention and management is provided along with background on sleep medicine and sleep surgery. Authored for ENT surgeons, head and neck specialists and neurologists, pneumonologists, sleep doctors as well for anesthesiologists, chapters offer solutions pulled from experts in the field of sleep surgery and information relevant to geographic areas worldwide.